A multicenter, double-blind, randomized, comparison study of the efficacy and safety of tigecycline to imipenem/cilastatin to treat complicated intra-abdominal infections in hospitalized subjects in China - Chen Y; Zhu D; Zhang Y; Zhao Y; Chen G; Li P; Xu L; Yan P; Hickman MA; Xu X; Tawadrous M; Wible M (Dove Medical Press, 2018)
Yijian Chen,1,2,* Demei Zhu,1,2,* Yingyuan Zhang,1,2 Yongjie Zhao,3 Gang Chen,4 Ping Li,5 Lihong Xu,6 Ping Yan,6 M Anne Hickman,7 Xiajun Xu,6 Margaret Tawadrous,7 Michele Wible7 1Institute of Antibiotics, Huashan Hospital Fudan University, Shanghai, China; 2Key Laboratory of Clinical Pharmacology of Antibiotics, National Health and Family Planning Commission, Shanghai, China; 3Department of General Surgery, Tianjin Union Medical Center, Tianjin, China; 4Department of Hepatobiliary Surgery, First People’s Hospital of Kunming, Kunming, China; 5Department of General Surgery, Sichuan Provincial People’s Hospital, Chengdu, China; 6Pfizer (China) Research & Development Co, Ltd, Shanghai, China; 7Pfizer Inc., Collegeville, PA, USA *These authors contributed equally to this work Purpose: To assess the efficacy and safety of tigecycline in treating complicated intra-abdominal infections (cIAIs) in hospitalized patients in China. Patients and methods: A Phase IV, multicenter, randomized, double-blinded, active-controlled, non-inferiority study was conducted. Hospitalized cIAI patients ≥18 years of age were randomized (1:1) to receive intravenous tigecycline (initial dose 100 mg, then 50 mg q12h) or imipenem/cilastatin (500 mg/500 mg or adjusted for renal dysfunction, q6h) for 5–14 days. The primary end point was clinical response for clinically evaluable (CE) subjects at test-of-cure (TOC) assessment. Results: Four hundred and seventy subjects were randomized; 232 in the tigecycline and 231 in the imipenem/cilastatin group were treated. Tigecycline was non-inferior to imipenem/cilastatin with respect to clinical response at TOC for all CE subjects, ie, the lower bound of the two-sided 95% CI (−12.0%, −1.4%) for the treatment difference in cure rate, tigecycline (89.9%) minus imipenem/cilastatin (96.6%), was >−15%. As non-inferiority was concluded in the CE population, superiority of tigecycline over imipenem/cilastatin and superiority of imipenem/cilastatin over tigecycline were tested on the CE and the modified intent-to-treat (mITT) populations according to pre-specified statistical criteria, and neither could be demonstrated (the cure rate was 82.8% vs 88.7%, difference -6.0% [−12.8%, 0.8%], for the mITT population). The subject-level microbiological response rate at TOC for the microbiologically evaluable population was 88.0% (110/125) vs 95.3% (102/107, difference -7.3% [−15.2%, 0.5%]). Nausea, drug ineffectiveness, postoperative wound infection, vomiting, and pyrexia were the most common adverse events in tigecycline-treated subjects; pyrexia, nausea, vomiting, and increased alanine aminotransferase and aspartate aminotransferase levels were most common in imipenem/cilastatin-treated subjects; none were unanticipated. Conclusion: Tigecycline was non-inferior to imipenem/cilastatin in treating hospitalized adult patients with cIAI. Superiority of tigecycline over imipenem/cilastatin or imipenem/cilastatin over tigecycline could not be demonstrated. Safety was consistent with the known profile for tigecycline. ClinicalTrials.gov identifier: NCT01721408. Keywords: tigecycline, imipenem/cilastatin, complicated intra-abdominal infections, non-inferiority